2008
DOI: 10.1111/j.1743-7563.2008.00159.x
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer and duration of using hormonal contraceptives

Abstract: Aim:To address the association between the duration of using oral contraceptives and cervical cancer, excluding HPV-DNA positive women. Methods: The sample consisted of 300 women over 30 years of age with newly diagnosed invasive cervical cancer who were admitted to the seven general hospitals in Tehran between 1 January 2005 and 31 December 2006. The control group consisted of 319 women in the same age group admitted to the same hospitals with conditions judged to be unrelated to any of the known or suspected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Therefore, this process resulted in 16 studies being identified as meeting the rigid inclusion criteria (Fig. ) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this process resulted in 16 studies being identified as meeting the rigid inclusion criteria (Fig. ) …”
Section: Resultsmentioning
confidence: 99%
“…The basic characteristics of selected studies in this meta‐analysis are displayed in Table . The final 16 case–control studies included 15 619 subjects (7433 cases and 8186 controls).…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies (5 good, 4 fair, 4 poor quality) evaluated the association between oral contraceptive use and cervical cancer incidence (63,65,66,69,70,73,(79)(80)(81)(82)(83)(84)(85)(86)(87), including 2 articles from an International Agency for Research on Cancer (IARC) study representing distinct populations (86,87). Of these, 9 were case-control studies, 3 were cohort studies, and 1 was a pooled analysis.…”
Section: Cervical Cancer Incidencementioning
confidence: 99%
“…In populations that were not selected for HPV-positive status, 6 case-control studies representing 5,436 women (73,79,81,82,84,85) and 3 cohort studies (63,65,69) representing 3,981,072 person-years met criteria for the meta-analysis examining ever versus never oral contraceptive use. Figure 3 shows results indicating increased odds of cervical cancer for women who had ever used oral contraceptives compared with women who never used oral contraceptives (OR, 1.21; CI, 0.91-1.61), but the comparison was not significant.…”
Section: Cervical Cancer Incidencementioning
confidence: 99%
“…Several epidemiological studies and a systematic review published in 2003 reported an association between HPVrelated cervical cancer and use of COCs; the data was not confirmed in a recent meta-analysis, suggesting that this association is related to the fact that condoms are seldom used in patients on CHCs, with a consequent higher incidence of HPV infections [47][48][49][50][51][52][53][54][55][56].…”
Section: Risks and Side Effects Of Chcsmentioning
confidence: 99%